Weaving Learning Processes by Means of ICTs: An Experience with Teachers from a Rural Area - Colindres Molina, Dilia (2013)
This article describes the results of a workshop developed with a group of elementary and high school teachers from the rural zone of Nicoya, where they had the opportunity to elaborate materials and teaching resources supported by information and communication technologies (ICT’s) that they later used in the development of their classes according to their different specialties. The process began with a diagnosis to understand the necessary training topics for the teachers from this zone. Then, the researchers met week by week in order to integrate technologies with the topics of the courses mentioned previously. Later, when the workshops were developed, the opinion of the teachers regarding the work done by the facilitators was evaluated, and the learning process was peer evaluated. In this way, the strengths and opportunities for improvement in the pedagogic mediation processes were identified. This methodology allowed for transformations to begin the learning processes, improving and positively impacting the student body, teachers, and the traditional curriculum that has always been used and to begin taking actions conducive to curriculum integration mediated by technologies.